Does God make a difference for student affairs? Emerging student affairs in the Christian story. (March 2020) - Glanzer, Perry L; Cockle, Theodore F; Graber, Britney; Jeong, Elijah
Despite a focus on the holistic formation of students, nonreligious narratives shape student affairs theories and professional practice guidelines. Recognizing this problem, Christian scholar-practitioners have authored a growing body of literature about what might be distinct about Christian student affairs. This article provides an analysis of the theological foundations used in this literature. Our aim was to locate the unique theological building blocks for a more comprehensive Christian theology of student affairs. Our analysis found that placing and practicing the profession of student affairs within the Christian narrative produced noteworthy distinctives in every aspect of student affairs.